Spectrum of germline mutations in RB1 in Chinese patients with retinoblastoma: Application of targeted next-generation sequencing - Zou, Yihua (Mol Vis, 2021)
PURPOSE: Retinoblastoma (RB) is a pediatric ocular malignancy due to biallelic inactivation of the RB1 gene. Genetic testing is critically important for treatment decisions for this disease. Targeted next-generation sequencing (NGS) has been demonstrated to be an effective strategy for discovering all types of mutations in the RB1 gene. The aim of this study is the application of targeted NGS in a cohort of Chinese patients with retinoblastoma to identify germline mutations in the RB1 gene. METHODS: Blood samples were collected from 149 unrelated probands with retinoblastoma (62 bilaterally and 87 unilaterally) and their parent(s). Genomic DNA was analyzed with custom panel-based targeted NGS, and the panel was designed to include exons 1–27 of the RB1 gene with flanking intronic sequences. Single nucleotide variations (SNVs) and small insertions/deletions (InDels) identified were confirmed with Sanger sequencing. If the Sanger sequencing of a low-frequency variant (LFV) detected with targeted NGS was negative, PCR-based deep NGS was conducted for added confirmation. Copy number variations (CNVs) detected with targeted NGS were confirmed with multiplex ligation-dependent probe amplification (MLPA). RESULTS: Overall, 74 germline mutations were detected in 48.3% of the probands (72/149, 56 bilateral and 16 unilateral cases). The total detection rate in the bilateral cases was 90.3% (56/62). These mutations included 64 SNVs and InDels (25 nonsense, 20 splicing, ten frameshift, eight missense, and one synonymous variants) and ten CNVs. All CNVs were confirmed with MLPA. Twenty-four (32.4%, 24/74) variants detected were novel, including nine splicing, six frameshift, five missense, and four nonsense variants. Eight LFVs (10.8%, 8/74) were found with targeted NGS; six of which were identified with Sanger sequencing, and two were identified with PCR-based deep NGS (13.16% and 3.000% mutant rates, respectively). CONCLUSIONS: This study expanded the spectrum of germline mutations in RB1 using targeted NGS technology, which is a cost-saving and efficient method for genetic sequencing of retinoblastoma and may improve the molecular diagnosis of retinoblastoma.